2021
DOI: 10.3390/healthcare9080993
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Nursing Competency and Psychological and Organizational Empowerment of Public Health Nurses: A Cross-Sectional Survey

Abstract: Aim: This study explored the effect of public health nurses’ current community care nursing competency on the psychological and organizational empowerment of public health services in Taiwan. Design: A cross-sectional nationwide survey design was used. Methods: A self-developed structured questionnaire was administered to public health nurses. They were recruited using a purposive sampling technique, and they participated in community healthcare workshops. Results: The mean score of Community Care Nursing Comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Additionally, the results of the present study demonstrated a significant positive relationship between clinical competency and psychological empowerment. This is coherent with other work that has demonstrated a relationship between the job performance of nurses with psychological empowerment and community health nursing competency with psychological and organisational empowerment of public health nurses (Kuo et al, 2021 ; Maynard et al, 2014 ). Therefore, professional preparedness and psychological empowerment should be included in disaster preparedness planning.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, the results of the present study demonstrated a significant positive relationship between clinical competency and psychological empowerment. This is coherent with other work that has demonstrated a relationship between the job performance of nurses with psychological empowerment and community health nursing competency with psychological and organisational empowerment of public health nurses (Kuo et al, 2021 ; Maynard et al, 2014 ). Therefore, professional preparedness and psychological empowerment should be included in disaster preparedness planning.…”
Section: Discussionsupporting
confidence: 90%
“…Psychological empowerment has been described as involving the four cognitive domains of meaning, self‐determination, competence and perceived impact (Ghasemi Hamzehkola & Naderi, 2019 ; Spreitzer, 1995 ). Prior studies have shown psychological empowerment as a relevant consideration for nurses with correlations to job satisfaction and work performance (Ebrahimi et al, 2013 ; Ghasemi Hamzehkola & Naderi, 2019 ; Kuo et al, 2021 ; Li et al, 2018 ; Mirkamli & Nastiezaie, 2010 ; Oducado, 2019 ; Zahednezhad et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The learning attitude scale includes four dimensions, namely learning attitude, self-efficacy, team efficacy, and collaborative learning. The nursing competence scale was employed to understand the community health care competencies of nursing students; it was developed after reference to the community care nursing competence scale (15 items) for nurses [ 6 ], which includes dimensions such as community understanding and community assessment skills. The scale items were scored on a 5-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…It was emphasized that encouraging health care professionals to view themselves as members of a global village is of great importance in a community. In order to respond to the increasing value attached to global and community health in the face of changes, and to nurture a competent and capable health care workforce, educational institutions should make adjustments in their curricula [ 6 ]. Nurses are mainly responsible for carrying out national public health policies, particularly in terms of health care and disease prevention [ 4 ].…”
Section: Introduction/backgroundmentioning
confidence: 99%
See 1 more Smart Citation